Other people's lives - Norton, Sheila (London Piatkus, 2003)
Beth was always certain that she was going to be somebody. However about to turn thirty she feels more like a nobody. Beth knows she wants more from life and while cleaning the elusive Alex Chapman's house she discovers how to get what she wants. The computer was just sitting there and it's time Beth dusted off some of her dreams.
UCWS-3306g donated by Ana P. Santos - January 2014
Keywords: Single mothers -- Fiction; Single mothers